2010
DOI: 10.1017/s1751731109990851
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stunning methods on product qualities in force-fed ducks and geese. 1. Carcass downgrading and meat quality

Abstract: This study investigated the effects of various stunning methods on the quality of carcass and meat in ducks and geese force-fed for the production of French ' foie gras'. The ducks (n 5 30 per group) were stunned with one of the following techniques: electrical stunning in a water bath (50 Hz AC, 130 mA, 4 s), head-only electrical stunning (50 Hz AC, 600 mA, 4 s), mechanical stunning (captive bolt) and controlled atmosphere stunning (CAS: phase 1, CO 2 (40%)-O 2 (30%)-N 2 (30%), for 2 min followed by phase 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
2
6
2
1
Order By: Relevance
“…Supporting the current result, similar L* value in male and female birds were reported by numerous authors for chicken 27,41 and for quail 48 . On the other hand, meat lightness values of the current study (40.15-40.59 for breast meat, 43.72-44.20 for thigh meat) were comparable with previous reports for geese meat 33,49 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Supporting the current result, similar L* value in male and female birds were reported by numerous authors for chicken 27,41 and for quail 48 . On the other hand, meat lightness values of the current study (40.15-40.59 for breast meat, 43.72-44.20 for thigh meat) were comparable with previous reports for geese meat 33,49 .…”
Section: Discussionsupporting
confidence: 91%
“…Supporting this result, Saláková et al 50 also reported significant influence of meat ultimate pH on meat redness. The redness values found in the current study (12.30-13.61 for breast meat, 9.79-10.38 for thigh meat) were lower than those reported by Okruszek et al 33 for Polish geese and by Fernandez et al 49 for French Landes grey breed. This difference indicate darker meat colour in Polish geese and French Landes grey breeds, and might be explained by difference in breed of geese, slaughter age and feeding system between studies.…”
Section: Discussioncontrasting
confidence: 80%
“…However, these results were higher than the reports of 19.2–20.5 by Fernandez et al . () for geese. The differences in cooking losses between the researches could be attributed to the differences in the cooking conditions, pH of the meat, muscle used and various other factors, which are often not reported.…”
Section: Resultsmentioning
confidence: 99%
“…En revanche, la résistance de la viande crue à une force de compression augmentait avec la durée d'attente sur quai (47,8 vs 37,8 N/cm 2 ). Fernandez et al (2010) ont comparé différentes techniques de narcose lors de l'abattage d'oies et de canards mulards gavés : électronarcose en bain (50 Hz en courant alternatif, 130 mA, 4 s), électronarcose bitemporale (50 Hz en courant alternatif, 600 mA, 4 s), étourdissement mécanique avec un pistolet à tige perforante et étourdissement en atmosphère modifiée (phase 1, 40% CO 2 -30% O 2 -30% N 2 ) pendant 2 min suivie de la phase 2, CO 2 > 85% dans l'air pendant 2 min). Chez les deux espèces, l'étourdissement en atmosphère modifiée était associé à une vitesse de chute du pH post-mortem plus lente et à une moindre accumulation d'acide lactique dans le magret.…”
Section: / Effet Des Conditions De Pré-abattage Et De La Technologie unclassified